2021
DOI: 10.1038/s41598-021-84342-2
|View full text |Cite
|
Sign up to set email alerts
|

Indirect effects of invasive rat removal result in recovery of island rocky intertidal community structure

Abstract: Eleven years after invasive Norway rats (Rattus norvegicus) were eradicated from Hawadax Island, in the Aleutian Islands, Alaska, the predicted three-level trophic cascade in the rocky intertidal, with native shorebirds as the apex predator, returned, leading to a community resembling those on rat-free islands with significant decreases in invertebrate species abundances and increases in fleshy algal cover. Rats had indirectly structured the intertidal community via their role as the apex predator in a four-le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…Invasive mammal eradication is a successful tool for conserving seabird populations and island ecosystems (Holmes et al., 2019; Jones et al., 2016; Kurle et al., 2021; Towns & Broome, 2003; Zavaleta et al., 2001 ). Removal of invasive species is just the first step in the ecosystem recovery process however, and recovery at a species or ecosystem level may not occur without assistance through active restoration (Jones & Schmitz, 2009; Kappes & Jones, 2014; Zavaleta et al., 2001 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Invasive mammal eradication is a successful tool for conserving seabird populations and island ecosystems (Holmes et al., 2019; Jones et al., 2016; Kurle et al., 2021; Towns & Broome, 2003; Zavaleta et al., 2001 ). Removal of invasive species is just the first step in the ecosystem recovery process however, and recovery at a species or ecosystem level may not occur without assistance through active restoration (Jones & Schmitz, 2009; Kappes & Jones, 2014; Zavaleta et al., 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring is consequentially sporadic, either not occurring at all or limited to select native species (Jones et al., 2016). Species counts alone may not reflect whole ecosystem condition (Levin, 1998), and cryptic ecosystem components and community or ecosystem level recovery may be too challenging to monitor (Kurle et al., 2021). Even for more visible species, capturing population trends can require repeat visits over decades, which in addition to being resource expensive raises issues of increased disturbance, and risks further breaches of biosecurity.…”
Section: Introductionmentioning
confidence: 99%
“…These local fishing communities not only practice sustainable management of their fisheries but they also care for and embrace a hands-on approach for island conservation and restoration [37]. PNA's island condition provides the cooperative with strong incentives to protect not only the marine resources it depends on but also the ecosystem it inhabits, because it is aware that any impact on the terrestrial ecosystem could impact the marine ecosystem, as recent research has revealed [58][59][60]. In this sense, the cooperative has become a strong steward of Cedros island and the San Benito Archipelago.…”
Section: Discussionmentioning
confidence: 99%
“…For example, removing invasive mammals confers resiliency to native populations via removal of competitors and/or predators, improving population attributes such as size, density, and growth rates [123]. Removing IAS can also improve both habitat quality and restore food web and trophic dynamics in terrestrial [62,[124][125][126] and marine environments [57,[127][128][129], important components in a healthy ecosystem that is resilient to climate change [130].…”
Section: Invasive Mammal Eradications and Ecosystem Resiliencementioning
confidence: 99%
“…For marine systems, a reduction in terrestrial erosion due to the removal of invasive mammals can also lead to a reduction of sedimentation on coral reefs, which can help ameliorate the effects of climate change on corals by improving water quality [153,154]. The removal of rats, a pervasive invasive omnivore on islands, was also shown to play a role in the resilience of nearshore marine systems, including in temperate and tropical latitudes [128,129,144]. Islands free of introduced predators have larger breeding seabird populations than nearby invaded islands, and these seabirds transport large amounts of nutrients from their feeding grounds in the open ocean to terrestrial and coastal systems [145,155,156].…”
Section: Invasive Mammal Eradications and Ecosystem Resiliencementioning
confidence: 99%